Hubungan Peran Kepala Ruangan dan Supervisor Keperawatan dengan Motivasi Perawat dalam Melakukan Dokumentasi Keperawatan - Peggy Passya; Ichsan Rizany; Herry Setiawan; Herry Setiawan (JURNAL KEPERAWATAN RAFLESIA, 2019)
NGood nursing documentation is inseparable from nurse motivation. Motivation of nurses is influenced internally and externally, one of them through the role of the head nursee and nurse supervisor To find out the relationship between the role of head nurses and nurse supervisor with the motivation of nurses in carrying out nursing documentation at Idaman Hospital in Banjarbaru City. The research used correlational study with a cross sectional approach and probability sampling technique with a type of simple random sampling. The sample in the study were 67 nurses in the inpatient room of Idaman Hospital, Banjarbaru City. Data retrieval was done by giving a questionnaire. Test analysis used Pearson correlation. The results of the study showed an average head role of 51.10, room supervisors averaged 32.81 and nurses' motivation averaged 33.61. These results indicate the head nurse and nurse supervisor often perform their roles and motivation of nurses is high. The results of the analysis found a positive relationship between the role of the head nurse and nurses' motivation in conducting nursing documentation in Idaman Hospital in Banjarbaru City (p Value = <0001;95%CI) and there was a positive relationship between the role of room supervisor and nurse motivation in conducting nursing documentation at RSD Idaman Banjarbaru City (p Value = <0001;95%CI). The role of the head nurse and the supervisor of the room can influence the level of motivation of nurses in conducting nursing documentation so that the head nurse and nurse supervisor are expected to perform their roles well.